Catalytic effect of Bi5+ in enhanced solar water splitting of tetragonal BiV0.8Mo0.2O4 - Wong, Lydia Helena (2017)
Improved photoelectrochemical activity for tetragonal BiV0.8Mo0.2O4 fabricated by hydrothermal synthesis is reported in the present study. The enhanced water oxidation efficiency is attributed to the formation of cation vacancies (Bi5+)/oxygen interstitials due to high amount of Mo doping. Efficient charge transport and electron hole separation for water oxidation using BiV0.8Mo0.2O4 photoanode was supported by electrochemical impedance investigations and open circuit photovoltage measurements. The present study gives a significant insight into the role of nonstoichiometry related efficient water oxidation using tetragonal BiVO4.